Nonverbal synchrony in subjects with hearing impairment and their significant others - Völter, Christiane; Oberländer, Kirsten; Mertens, Sophie; Ramseyer, Fabian T. (Frontiers in Psychology, 2022)
Introduction Hearing loss has a great impact on the people affected, their close partner and the interaction between both, as oral communication is restricted. Nonverbal communication, which expresses emotions and includes implicit information on interpersonal relationship, has rarely been studied in people with hearing impairment (PHI). In psychological settings, nonverbal synchrony of body movements in dyads is a reliable method to study interpersonal relationship. Material and Methods A 10-minute social interaction was videorecorded in 39 PHI (29 spouses and 10 parent-child dyads) and their significant others (SOs). Nonverbal synchrony, which means the nonverbal behaviors of two interacting persons (referring to both general synchrony and the role of leading) and verbal interaction (percentage of speech, frequency of repetitions and queries) were analyzed by computer algorithms and observer ratings. Hearing-related quality of life, coping mechanisms, general psychopathology, quality of relationship, and burden of hearing loss experienced by SOs were assessed using questionnaires. Results In the 39 dyads, true nonverbal synchrony differed from pseudosynchrony (t(43.4) = 2.41; p = 0.02) with a medium effect size (d=0.42). Gender of PHI had a significant effect on general synchrony (p=0.025) and on leading by SOs (p=0.017). Age gap correlated with synchronic movements (p=0.047). Very short duration of hearing impairment was associated with lower nonverbal synchrony in the role of leading by SOs (p=0.031). Feeling of closeness by PHI correlated negatively with the role of leading by SOs (p>0.001) and feeling of closeness by SOs was positively associated with leading by PHI (p=0.015). No correlation was detected between nonverbal synchrony and other questionnaires. Burden experienced by the SOs was higher in SOs who reported less closeness (p=0.014). Discussion A longer hearing impairment leads to more nonverbal leading by SOs compared to PHI with very short duration of hearing loss, possibly because of the long-lasting imbalance in communication. If PHI felt more closeness, SOs led less and vice versa. Burden experienced by SOs negatively correlated with closeness reported by SOs. Use of nonverbal signals and communication might help to improve benefits of auditory rehabilitation for PHI and decrease burden experienced by SOs.